Polishing pad and manufacturing method of polishing pad
By using specific base material in the polishing pad to ensure its specific performance in compression testing and dynamic viscoelastic measurements, the problem of edge-profile exceptions in the prior art is solved, and a more stable pollution performance is achieved.
Patent Information
- Application Number
- JP2024164911
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-29
- Filing Date
- 2024-09-24
- Publication Date
- 2025-04-10
Smart Images

Figure 2025060447000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a polishing pad. In particular, the present invention relates to a polishing pad that can be suitably used for polishing optical materials, semiconductor wafers, semiconductor devices, substrates for hard disks, etc. In particular, the present invention is suitably used for polishing devices in which an oxide layer, a metal layer, etc. are formed on a semiconductor wafer. [Background technology]
[0002] Polishing of semiconductor wafers and the like is usually performed using a technique known as CMP, in which a polishing pad and the wafer are slid relative to each other under pressure while a slurry (polishing liquid) is supplied between them to flatten the wafer surface through a combined chemical and mechanical polishing action.
[0003] The CMP method will be described with reference to FIG. 1. As shown in FIG. 1, a polishing apparatus 1 for carrying out the CMP method is provided with a polishing pad 3, which is in contact with a polished object 8 held by a holding platen 16 and a retainer ring (not shown in FIG. 1) for holding the polished object 8 so as not to shift, and includes a polishing layer 4, which is a layer for polishing, and a base layer 6 for supporting the polishing layer 4. The polishing pad 3 is rotated while the polished object 8 is pressed against it, and polishes the polished object 8. At that time, a slurry 9 is supplied between the polishing pad 3 and the polished object 8. The slurry 9 is a mixture (dispersion liquid) of water, various chemical components, and hard fine abrasive grains, and the chemical components and abrasive grains in the slurry are flowed and move relative to the polished object 8, thereby increasing the polishing effect. The slurry 9 is supplied to the polishing surface through grooves or holes and discharged.
[0004] Incidentally, the polishing pad 3 has conventionally been one that uses polyurethane foam for the polishing layer 4, but this can cause profile abnormalities in the workpiece 8, particularly in the edge portion, which is the periphery of the workpiece 8. Abnormalities in edge profiles are known to occur in oxide film polishing, such as over-polishing, where the edge of the workpiece is polished more than the center, and a polishing defect called rebound, where unevenness appears on the periphery a little inside the edge. Also, when polishing a workpiece that has a metal film such as a Cu film (damascene structure), a polishing defect occurs in which the edge of the workpiece is not polished as much as the center, resulting in a "spring shape."
[0005] Patent Document 1 discloses a polishing pad that prevents "edge sagging" while suppressing the occurrence of polishing scratches by controlling the hardness of the polishing layer within a certain range by making the structure of the bubbles in the foam specific. Patent Document 2 discloses a polishing pad that does not have the problem of "edge sagging" by setting the hardness and tear strength of the polishing layer within a specified range. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2012-714 A [Patent Document 2] JP 2016-190313 A Summary of the Invention [Problem to be solved by the invention]
[0007] However, the polishing pads described in Patent Documents 1 and 2 above require specific physical properties and bubble structures of the polishing layer, and even if the "edge droop" is improved, other polishing performance may be inferior. In addition, although the "edge droop" is improved, there is no mention of improving the "flare shape", which is another edge profile abnormality.
[0008] The present invention has been made in consideration of the above problems, and aims to provide a polishing pad that enables improvement of the wave shape without significantly changing the physical properties and bubble structure of the polishing layer. [Means for solving the problem]
[0009] In view of the above problems, the present inventors conducted extensive research and discovered that the "flared shape" can be improved by using a specific base layer, thereby completing the present invention. That is, the present invention includes the following. [1] A polishing pad comprising a polishing layer having a polishing surface for polishing an object to be polished, and a base layer disposed on the opposite side of the polishing surface of the polishing layer, The base layer has a compressive deformation of 20 μm or less in a compression test using MAG, The storage modulus in dynamic viscoelasticity measurement in compression mode is 3.5 MPa or more and 20 MPa or less. A polishing pad, wherein the thickness of the base layer is 40% or more and less than 65% of the thickness of the polishing layer. [2] The polishing pad according to claim 1, characterized in that the ratio of the storage modulus of the polishing layer to the storage modulus of the base layer (polishing layer / base layer) is 5 or more and 30 or less. [3] The polishing pad according to [1], wherein the base layer is made of a polyurethane foam or a polyurethane material having hollow microspheres dispersed therein. [4] The polishing pad according to [1], which is a polishing pad for polishing metal. [5] A polishing method for polishing a workpiece having a metal surface, comprising the steps of: Providing an object to be polished having a metal surface; and bringing the polishing surface of the polishing pad according to claim 1 into contact with the metal surface to polish the metal surface. Effect of the Invention
[0010] The polishing pad of the present invention uses a highly resilient material for the base layer, which has a compressive deformation of 20 μm or less in a compression test using MAG and a storage modulus of 3.5 MPa to 20 MPa in a dynamic viscoelasticity measurement in a compression mode, thereby suppressing edge profile abnormalities (especially the shape of a metal film). In addition, the intrusion of slurry into the base layer can be suppressed, and peeling between the polishing layer and the base layer can be suppressed, and changes in compression behavior over time due to the voids inside the base being replaced by water can be suppressed. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 is a perspective view of a polishing apparatus 1. As shown in FIG. [Diagram 2] FIG. 2 is a perspective view of a polishing pad 3 of the present invention. [Diagram 3] FIG. 3 is a cross-sectional view of the polishing target 8 in a fin-shaped state. [Figure 4] FIG. 4 is a film thickness profile of a polishing pad according to the prior art, showing a method for measuring the film thickness difference. [Diagram 5] FIG. 5 shows the change in thickness profile of the Cu film using a conventional polishing pad. [Figure 6] FIG. 6 shows the thickness profile of the Cu film at the edge of the object 8 to be polished using the polishing pads 3 of Examples 1 to 4 and Comparative Examples 1 and 2. As shown in FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, a mode for carrying out the invention will be described, however, the present invention is not limited to the mode for carrying out the invention.
[0013] <<Polishing pad>> The structure of the polishing pad 3 will be described with reference to Fig. 2. As shown in Fig. 2, the polishing pad 3 includes a polishing layer 4 and a base layer 6. The shape of the polishing pad 3 is preferably disc-shaped, but is not particularly limited, and the size (diameter) can also be appropriately determined depending on the size of the polishing apparatus 1 equipped with the polishing pad 3, and can be, for example, about 10 cm to 2 m in diameter. In the polishing pad 3 of the present invention, the polishing layer 4 is preferably bonded to the base layer 6 via an adhesive layer 7, as shown in FIG. The polishing pad 3 is attached to a polishing platen 10 of the polishing apparatus 1 by a double-sided tape or the like arranged on a base layer 6. As shown in FIG. 1, the polishing pad 3 is rotated by the polishing apparatus 1 while pressing against an object 8 to be polished, and polishes the object 8 to be polished.
[0014] Here, we will explain the wavy shape, which is an abnormality in the edge profile. The wavy shape is a polishing defect phenomenon in which the edge portion of the polished object 8 is not polished as much as the central portion. Figure 3 is a cross-sectional view of the polished object 8, and it can be seen that the disk-shaped polished object 8 has an edge portion (end portion) 8a that is not polished as much as the central portion. This is the wavy shape. Note that in Figure 3, the wavy shape is depicted enlarged for ease of understanding. In this specification, the strength of the ripple shape is expressed by measuring the film thickness of the thin film when the polished object 8 has a thin film such as Cu. Figure 4 shows the film thickness difference caused by the ripple shape, and is a profile of the polished object 8 showing a typical ripple shape when a conventional polishing pad is used. As shown in Figure 4, the film thickness difference is the distance from the thickest film thickness at the end of the polished object 8 to the thinnest film thickness. When the polished object 8 does not have a thin film, the profile of the entire thickness of the polished object 8 is measured, and the difference between the thickest and thinnest end portions is calculated and evaluated in the same manner as in Fig. 4. In this specification, for convenience, the ripple shape is evaluated using the film thickness difference in the polished object 8 having a Cu thin film.
[0015] FIG. 5 shows the thickness profile of the Cu film (FIG. 5-1, FIG. 5-3, FIG. 5-5) in which the vertical axis is the thickness of the Cu film and the horizontal axis is the distance along a line passing through the center of the polished object 8 (the center of the polished object 8 is set to 0, and the part 140-150 mm from the center) for the polished object 8 having a Cu coating polished by a conventional polishing pad, and the polishing rate profile (FIG. 5-2, FIG. 5-4) in which the vertical axis is the polishing rate (RR) and the horizontal axis is the distance along a line passing through the center of the polished object 8 (the center of the polished object 8 is set to 0, and the part 140-150 mm from the center) for the polished object 8. As can be seen from the thickness profile of the Cu film before polishing in FIG. 5-1, the Cu film originally has a slightly jumping shape in which the film thickness at the edge part becomes suddenly thicker. That is, the film thickness at the edge part is thicker than the other parts by about 1500 angstroms (hereinafter, the difference between the film thickness at the edge part and the film thickness at the other parts is referred to as the film thickness difference). Figure 5, 2 (top right) shows the polishing rate profile after the first polishing, where the polishing rate of the edge portion is about 1200 angstroms faster than the other portions. Figure 5, 3 (middle left) shows the thickness profile of the Cu film after the first polishing, where it can be seen that the film thickness difference has decreased to about 1000 angstroms. Figure 5, 4 (middle left) shows the polishing rate profile after polishing again (second time), where the polishing rate of the edge portion is 300 angstroms faster than that slightly inside the edge portion (147 mm part), but is about the same as that of the portion closer to the center (142 mm or less). Figure 5, 5 (bottom) shows the thickness profile of the Cu film after polishing twice, where the film thickness difference remains at 1000 angstroms, and the 1000 angstrom ridge shape still remains. That is, even when polishing is performed multiple times with a conventional polishing pad, no improvement is observed in the film thickness difference of the resulting polished object 8, and the film thickness difference is not desirable. It should be noted that the "flared shape" can be problematic in semiconductor polishing (particularly the process of polishing metal films) when the difference in film thickness between the outermost edge (peripheral) part of the workpiece 8 and other parts of the workpiece 8 exceeds 350 angstroms. Therefore, in this specification, a flared shape where the difference in film thickness exceeds 350 angstroms is considered to be a flared shape that needs to be improved.
[0016] <Polishing layer> (composition) The polishing pad 3 includes a polishing layer 4 that is a layer for polishing an object to be polished 8. The material constituting the polishing layer 4 can be suitably selected from polyurethane resin, polyurea resin, and polyurethane-polyurea resin, and more preferably polyurethane resin. The size (diameter) of the polishing layer 4 is the same as that of the polishing pad 3 and can be about 10 cm to 2 mm in diameter, and the thickness of the polishing layer 4 can usually be about 1 to 5 mm. The polishing layer 4 is rotated together with the polishing platen 10 of the polishing device 1, and while a slurry 9 is poured onto it, the chemical components and abrasive grains contained in the slurry 9 are moved relative to the object 8 to be polished, thereby polishing the object 8 to be polished.
[0017] (grooving, embossing) It is preferable that the surface of the polishing layer 4 of the present invention facing the polished object 8 is grooved or embossed. The groove is not particularly limited, and may be either a slurry discharge groove communicating with the periphery of the polishing layer 4 or a slurry holding groove not communicating with the periphery of the polishing layer 4, or may have both a slurry discharge groove and a slurry holding groove. Examples of the slurry discharge groove include lattice grooves and radial grooves, and examples of the slurry holding groove include concentric grooves and perforations (through holes), and these may also be combined. In low-pressure polishing, the platen is rotated at high speed in order to reduce the pressing force against the workpiece 8 and to ensure the polishing rate. This may cause the so-called hydroplaning phenomenon, in which the slurry 9 exists in a layer between the polishing surface and the processing surface and interferes with the polishing process. This phenomenon can be suppressed by groove processing or embossing the polishing surface. It is also possible to promote the discharge of polishing waste and the movement of the polishing liquid. The cross-sectional shape may be U-shaped, V-shaped, or semicircular. There is no particular restriction on the pitch, width, and depth of the grooves. In addition, in order to improve the flatness of the polishing pad 3, a surface grinding process such as buffing may be performed on the polishing surface side or the surface opposite to the polishing surface of the polishing pad 3.
[0018] The polishing layer 4 is formed by casting a mixture of a urethane prepolymer obtained by reacting an isocyanate group-containing compound with a polyol compound, hollow microspheres, and a curing agent (chain extender), and slicing the cured foam. That is, the polishing layer 4 is dry molded.
[0019] The voids formed inside the polishing layer 4 are formed to have a substantially circular cross section by the hollow microspheres added to the dispersion liquid during dry molding. That is, in the polishing layer 4, a plurality of hollow microspheres are formed so as to overlap in the thickness direction, and can be formed substantially uniformly in two directions intersecting the thickness direction. Since the polishing layer 4 is formed by slicing a foam, some or all of the hollow microspheres may be open on the polishing surface. The average opening diameter of the openings formed on the polishing surface is adjusted to a range of 10 to 100 μm.
[0020] (Shore D hardness) The Shore D hardness of the polishing layer 4 of the present invention is not particularly limited, but is preferably 40 to 70. If the Shore D hardness is less than 40 degrees, it becomes difficult to flatten fine irregularities by low-pressure polishing. If it exceeds 70 degrees, the polishing particles are strongly rubbed against the polished object 8, and scratches may occur on the processed surface of the polished object 8. The lower limit of the Shore D hardness of the polishing layer 4 is preferably 40 or more, 42 or more, and 45 or more, in that order, and the upper limit is preferably 70 or less, 65 or less, and 60 or less, in that order.
[0021] (Poisson's ratio) The Poisson's ratio of the polishing layer 4 is not particularly limited. The Poisson's ratio of the polishing layer 4 is, for example, 0.20 to 0.50, and preferably 0.30 to 0.40. If the Poisson's ratio of the polishing layer 4 is smaller than 0.20, it may not show sufficient elasticity and the polishing rate may decrease. In addition, the upper limit of the Poisson's ratio is 0.5, and a material with a Poisson's ratio close to 0.5 is a special material such as a rubber material, which has strong water repellency and cannot hold polishing slurry, etc.
[0022] The abrasive layer 4 preferably comprises hollow microspheres.
[0023] <Base material layer> (composition) The polishing pad 3 of the present invention has a base layer 6. Although the base layer may be called a cushion layer in the art, it will be called a base layer in this specification. The base layer 6 makes the contact of the polishing layer 4 with the workpiece 8 more uniform.
[0024] The substrate layer 6 used in the present invention is preferably made of a polyurethane foam or a polyurethane material having hollow microspheres dispersed therein. Polyurethane foam is a homogeneous plastic foam obtained by mixing polyisocyanate having NCO (isocyanate) groups and polyol having OH (hydroxy) groups together with a catalyst, blowing agent, foam stabilizer, etc., and simultaneously carrying out a foaming reaction and a resinification reaction. Examples of flexible polyurethane foam and rigid polyurethane foam are flexible polyurethane foam, which has interconnected cells, is soft and has good restorability, and generally has an expansion ratio of 60 to 100 times and an apparent density of 16 to 100 kg / m. 3 A rigid polyurethane foam is a plastic foam made of small air bubbles, each of which is an independent bubble. Rigid polyurethane foam is preferable because it has a small amount of compression deformation, high resilience, and excellent bounce shape improvement performance.
[0025] The polyurethane material with hollow microspheres dispersed therein is a foam obtained by casting and hardening a mixture of an isocyanate group-containing compound mixed with hollow microspheres and a curing agent (chain extender), as described for the polishing layer 4. The hollow microspheres refer to microspheres having voids inside. The shapes of the hollow microspheres include spherical, elliptical, and shapes similar thereto. Examples include those that have already been expanded, and those that have been added with unexpanded heat-expandable microspheres at the raw material mixing stage and then heated and expanded. The physical properties of the base layer 6, such as its A hardness, can be adjusted to fall within a desired range by adjusting the composition of the base layer 6, the number and size of the hollow microspheres, and the like.
[0026] When the base layer 6 used in the present invention is made of a polyurethane material having hollow microspheres dispersed therein, the base layer 6 has closed cells rather than interconnected cells, which prevents the intrusion of slurry and the like into the base layer 6 and inhibits peeling between the polishing layer 4 and the base layer 6. This also inhibits changes in compression behavior over time due to the voids inside the base layer 6 turning into water.
[0027] (Compressive deformation amount) The base layer 6 has a compressive deformation of 20 μm or less in a compression test using MAG. The compressive deformation is determined by subtracting the thickness of the base layer at a predetermined number of compressions after repeated compression / recovery from the thickness of the base layer before the test. The predetermined number of compressions is preferably 10 to 200 times, more preferably 20 to 100 times. If the compressive deformation exceeds 20 μm, there is a risk that the edge profile improvement performance will not be sufficient. The compressive deformation is preferably 18 μm or less, more preferably 16 μm or less. The compression test using MAG is a continuous compression / recovery test performed using MAG (Micro Autograph, Shimadzu Corporation, MST-1).
[0028] (Storage modulus) The base layer 6 has a storage modulus of 3.5 MPa or more and 20 (20.0) MPa or less in a dynamic viscoelasticity test (DMA) in a compression mode. If the storage modulus is less than 3.5 MPa, there is a risk that the performance of improving the shape of the blade will not be sufficient, and if the storage modulus is more than 20 MPa, there is a risk that other polishing performances, such as an increase in scratches on the polished object 8, will be adversely affected. The lower limit of the storage modulus is preferably 4.0 MPa, and more preferably 4.5 MPa. The upper limit is preferably 15.0 MPa, and more preferably 12.5 MPa. The dynamic viscoelasticity test (DMA) is a method for measuring the mechanical properties of a sample by applying a strain or stress that changes (oscillates) over time to the sample and measuring the stress or strain that occurs as a result.
[0029] (Ratio of storage modulus between polishing layer and base layer) The ratio of the storage modulus (MPa) of the polishing layer 4 to the storage modulus (MPa) of the base layer 6 (polishing layer / base layer) is 5 or more and 30 or less. If the ratio of the storage modulus of the polishing layer 4 to the storage modulus of the base layer 6 (polishing layer / base layer) is less than 5, the base layer may not exhibit sufficient cushioning performance, and if the ratio of the storage modulus of the polishing layer 4 to the storage modulus of the base layer 6 (polishing layer / base layer) is greater than 30, the base layer may not exhibit sufficient spring shape improvement performance. The lower limit of the ratio of the storage modulus of the polishing layer 4 to the storage modulus of the base layer 6 (polishing layer / base layer) is preferably 7.5, more preferably 10. The upper limit is preferably 25, more preferably 20.
[0030] (ratio of base layer thickness to polishing layer thickness) The ratio of the thickness (mm) of the base layer 6 to the thickness (mm) of the polishing layer 4 is 40% or more and less than 65%. If the ratio of the thickness of the base layer 6 to the thickness of the polishing layer 4 is less than 40%, the base layer may not exhibit sufficient cushioning performance, and if the ratio of the thickness of the base layer 6 to the thickness of the polishing layer 4 is 65% or more, the base layer may not exhibit sufficient performance to improve the shape of the blade. The lower limit of the ratio of the thickness of the base layer 6 to the thickness of the polishing layer 4 is preferably 45%, more preferably 50%. The upper limit is preferably 65%, more preferably 62.5%.
[0031] (Shore A hardness) The Shore A hardness of the base layer 6 is not particularly limited, but is preferably, for example, 50 to 80. If the Shore A hardness is less than 50, there is a risk that the edge profile improving performance will not be sufficiently exhibited, and if it exceeds 80, there is a risk that the base layer will not exhibit a certain degree of cushioning property required.
[0032] (density) The density of the base layer 6 is not particularly limited. For example, the density is 0.10 to 0.80 g / cm. 3In addition, when air bubbles are contained, the density referred to here is not the density of the material itself but the density of the base material layer 6 in a state in which air bubbles are contained.
[0033] <Adhesive layer> The adhesive layer 7 is a layer for adhering the base layer 6 and the polishing layer 4, and is usually made of a double-sided tape or adhesive. The double-sided tape or adhesive may be any known double-sided tape or adhesive in the art (e.g., an adhesive sheet). The polishing layer 4 and the base layer 6 are bonded together by an adhesive layer 7. The adhesive layer 7 can be made of at least one adhesive selected from, for example, acrylic, epoxy, and urethane adhesives. For example, an acrylic adhesive is used, and the thickness can be set to 0.1 mm.
[0034] <<Polishing pad manufacturing method>> A method for producing the polishing pad 3 of the present invention will now be described.
[0035] <Abrasive layer material> The material of the polishing layer 4 is not particularly limited, but for example, the main component is preferably a polyurethane resin, a polyurea resin, or a polyurethane polyurea resin, and more preferably a polyurethane resin. Specific examples of the main component material include a material obtained by reacting a urethane bond-containing polyisocyanate compound with a curing agent.
[0036] Hereinafter, a method for producing the material of the polishing layer 4 will be described using an example in which a urethane bond-containing isocyanate compound, a polyol compound, and a curing agent are used.
[0037] Examples of a method for producing the polishing layer 4 using a urethane bond-containing polyisocyanate compound and a curing agent include a production method including: a material preparation step of preparing at least a urethane bond-containing polyisocyanate compound, an additive, and a curing agent; a mixing step of mixing at least the urethane bond-containing polyisocyanate compound, the additive, and the curing agent to obtain a mixed liquid for molding a molded body; and a curing step of molding the mixed liquid for molding a molded body into the polishing layer 4.
[0038] The material preparation process, the mixing process, and the molding process will be explained below.
[0039] <Material preparation process> To manufacture the polishing layer 4 of the present invention, a urethane bond-containing polyisocyanate compound and a curing agent are prepared as raw materials for a polyurethane resin molded body (cured resin). Here, the urethane bond-containing polyisocyanate is a urethane prepolymer for forming a polyurethane resin molded body. When the polishing layer 4 is to be a polyurea resin molded body or a polyurethane-polyurea resin molded body, a prepolymer appropriate for the purpose is used.
[0040] Each component will be described below.
[0041] (Polyisocyanate compound containing urethane bonds) The urethane bond-containing polyisocyanate compound (urethane prepolymer or simply prepolymer) is a compound obtained by reacting the following polyisocyanate compound with a polyol compound under commonly used conditions, and contains a urethane bond and an isocyanate group in the molecule. In addition, other components may be contained in the urethane bond-containing polyisocyanate compound within the range that does not impair the effects of the present invention.
[0042] The urethane bond-containing polyisocyanate compound may be a commercially available product, or may be a product synthesized by reacting a polyisocyanate compound with a polyol compound. The reaction is not particularly limited, and addition polymerization may be performed using a method and conditions known in the production of polyurethane resins. For example, the polyisocyanate compound may be added to a polyol compound heated to 40°C while stirring in a nitrogen atmosphere, and the temperature may be raised to 80°C after 30 minutes, and the reaction may be continued at 80°C for 60 minutes. The urethane bond-containing polyisocyanate preferably has an NCO equivalent of about 300 to 600. Therefore, when the urethane bond-containing polyisocyanate is a commercially available product, it is preferable that the NCO equivalent falls within the above range, and when it is produced by synthesis, it is preferable to adjust the NCO equivalent to the above range by using the following raw materials in an appropriate ratio.
[0043] (Polyisocyanate compounds) In this specification, the polyisocyanate compound means a compound having two or more isocyanate groups in the molecule. The polyisocyanate compound is not particularly limited as long as it has two or more isocyanate groups in the molecule. For example, diisocyanate compounds having two isocyanate groups in the molecule include m-phenylene diisocyanate, p-phenylene diisocyanate, 2,6-tolylene diisocyanate (2,6-TDI), 2,4-tolylene diisocyanate (2,4-TDI), naphthalene-1,4-diisocyanate, diphenylmethane-4,4'-diisocyanate (MDI), 4,4'-methylene-bis(cyclohexyl isocyanate) (hydrogenated MDI), 3,3'-dimethoxy-4,4'-biphenyl diisocyanate, 3,3'-dimethyl- Examples of the polyisocyanate include diphenylmethane-4,4'-diisocyanate, xylylene-1,4-diisocyanate, 4,4'-diphenylpropane diisocyanate, trimethylene diisocyanate, hexamethylene diisocyanate, propylene-1,2-diisocyanate, butylene-1,2-diisocyanate, cyclohexylene-1,2-diisocyanate, cyclohexylene-1,4-diisocyanate, p-phenylene diisothiocyanate, xylylene-1,4-diisothiocyanate, ethylidine diisothiocyanate, etc. These polyisocyanate compounds may be used alone or in combination of a plurality of polyisocyanate compounds.
[0044] The polyisocyanate compound preferably contains 2,4-TDI and / or 2,6-TDI.
[0045] (Polyol compounds as raw materials for prepolymers) In this specification, the polyol compound means a compound having two or more hydroxyl groups (OH) in the molecule. Examples of polyol compounds used in the synthesis of the urethane bond-containing polyisocyanate compound as a prepolymer include diol compounds, triol compounds, etc., such as ethylene glycol, diethylene glycol (DEG), butylene glycol, polyether polyol compounds, such as poly(oxytetramethylene) glycol (or polytetramethylene ether glycol) (PTMG), polyester diols, and combinations thereof. Among these, it is preferable to use polypropylene glycol, polyester diol, and diethylene glycol in combination. The polyester diol can be obtained, for example, by reacting a dicarboxylic acid compound with a diol compound. Examples of the dicarboxylic acid compound include aliphatic dicarboxylic acids such as succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, decanedioic acid, and dodecanedioic acid; unsaturated bond-containing dicarboxylic acids such as maleic anhydride, maleic acid, and fumaric acid; alicyclic polycarboxylic acids such as 1,3-cyclopentanedicarboxylic acid and 1,4-cyclohexanedicarboxylic acid; and aromatic dicarboxylic acids such as orthophthalic acid, terephthalic acid, isophthalic acid, 1,4-naphthalenedicarboxylic acid, 2,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, naphthalic acid, biphenyldicarboxylic acid, diphenic acid, and anhydrides thereof; and the like, which may be used alone or in combination. Examples of diol compounds used in the synthesis of polyester diols include ethylene glycol, diethylene glycol, triethylene glycol, 1,2-propanediol, 1,3-propanediol, 2-methyl-1,3-propanediol, 1,3-butanediol, 1,4-butanediol, neopentyl glycol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, and 1,6-hexanediol, and these can be used alone or in combination. Among the above, polyester diols of adipic acid and 1,4-butanediol, and polyester diols of adipic acid and diethylene glycol are preferred. The number average molecular weight (Mn) of the polyol compound is not particularly limited, and can be, for example, 500 to 2500. Here, the number average molecular weight can be measured by gel permeation chromatography (GPC). When measuring the number average molecular weight of the polyol compound from the polyurethane resin, it can also be estimated by GPC after decomposing each component by a conventional method such as amine decomposition. The above polyol compounds may be used alone or in combination of two or more.
[0046] (Additives) As described above, additives such as an oxidizing agent may be added to the material of the polishing layer 4 as necessary.
[0047] (hardening agent) In the method for producing the polishing layer 4 of the present invention, a curing agent (also called a chain extender) is mixed with a urethane bond-containing polyisocyanate compound, etc. in a mixing step. By adding the curing agent, in the subsequent molding step, the main chain terminal of the urethane bond-containing polyisocyanate compound bonds with the curing agent to form a polymer chain, which then hardens. Examples of the curing agent include ethylenediamine, propylenediamine, hexamethylenediamine, isophoronediamine, dicyclohexylmethane-4,4'-diamine, 3,3'-dichloro-4,4'-diaminodiphenylmethane (MOCA), 4-methyl-2,6-bis(methylthio)-1,3-benzenediamine, 2-methyl-4,6-bis(methylthio)-1,3-benzenediamine, 2,2-bis(3-amino-4-hydroxyphenyl)propane, 2,2-bis[3-(isopropylamino)-4- polyamine compounds such as 2,2-bis[3-(1-methylpropylamino)-4-hydroxyphenyl]propane, 2,2-bis[3-(1-methylpentylamino)-4-hydroxyphenyl]propane, 2,2-bis(3,5-diamino-4-hydroxyphenyl)propane, 2,6-diamino-4-methylphenol, trimethylethylene bis-4-aminobenzoate, and polytetramethylene oxide-di-p-aminobenzoate; ethylene glycol, Pyrene glycol, diethylene glycol, trimethylene glycol, tetraethylene glycol, triethylene glycol, dipropylene glycol, 1,4-butanediol, 1,3-butanediol, 2,3-butanediol, 1,2-butanediol, 3-methyl-1,2-butanediol, 1,2-pentanediol, 1,4-pentanediol, 2,4-pentanediol, 2,3-dimethyltrimethylene glycol, tetramethylene glycol, 3-methyl-4,3-pentanediol, 3- Examples of polyhydric alcohol compounds include methyl-4,5-pentanediol, 2,2,4-trimethyl-1,3-pentanediol, 1,6-hexanediol, 1,5-hexanediol, 1,4-hexanediol, 2,5-hexanediol, 1,4-cyclohexanedimethanol, neopentyl glycol, glycerin, trimethylolpropane, trimethylolethane, trimethylolmethane, poly(oxytetramethylene) glycol, polyethylene glycol, and polypropylene glycol.The polyamine compound may have a hydroxyl group, and examples of such amine compounds include 2-hydroxyethylethylenediamine, 2-hydroxyethylpropylenediamine, di-2-hydroxyethylethylenediamine, di-2-hydroxyethylpropylenediamine, 2-hydroxypropylethylenediamine, di-2-hydroxypropylethylenediamine, etc. As the polyamine compound, a diamine compound is preferable, and it is more preferable to use, for example, 3,3'-dichloro-4,4'-diaminodiphenylmethane (methylenebis-o-chloroaniline) (hereinafter abbreviated as MOCA).
[0048] (Hollow microspheres) The polishing layer 4 may contain hollow microspheres having an outer shell and hollow inside, if necessary. As described above, the material of the hollow microspheres may be commercially available. Alternatively, a material obtained by synthesis using a conventional method may be used. The material of the outer shell of the hollow microspheres is not particularly limited, and examples thereof include polyvinyl alcohol, polyvinylpyrrolidone, poly(meth)acrylic acid, polyacrylamide, polyethylene glycol, polyhydroxyether acrylate, maleic acid copolymer, polyethylene oxide, polyurethane, poly(meth)acrylonitrile, polyvinylidene chloride, polyvinyl chloride and organic silicone resins, and copolymers of two or more kinds of monomers constituting these resins. In addition, examples of commercially available hollow microspheres include, but are not limited to, Expancel series (trade name manufactured by Akzo Nobel), Matsumoto Microsphere (trade name manufactured by Matsumoto Yushi Co., Ltd.), etc. The gas contained in the hollow microspheres is not particularly limited, but may be, for example, a hydrocarbon, specifically, isobutane.
[0049] <Mixing process> In the mixing step, the urethane bond-containing polyisocyanate compound (urethane prepolymer) obtained in the preparation step, hollow microspheres, additives, and curing agent are fed into a mixer and stirred and mixed. The mixing step is carried out in a state where the components are heated to a temperature at which the fluidity of each component can be ensured.
[0050] <Forming process> In the molding process, the mixture for molding prepared in the mixing process is poured into a rod-shaped mold preheated to 30 to 100°C for primary curing, and then heated at about 100 to 150°C for about 10 minutes to 5 hours for secondary curing to form a cured polyurethane resin (polyurethane resin molded body). At this time, the urethane prepolymer and the curing agent react to form a polyurethane resin, and the mixture hardens.
[0051] In the molding process, the mixture is reacted in a mold as necessary to form a foam. At this time, the prepolymer is crosslinked and hardened by the reaction between the prepolymer and the hardener.
[0052] After obtaining the molded body, it is sliced into sheets to form a plurality of polishing layers 4. A general slicing machine can be used for slicing. During slicing, the lower layer portion of the polishing layer 4 is held, and the polishing layer 4 is sliced to a predetermined thickness starting from the upper layer portion. The slice thickness is set to a range of, for example, 1.3 to 2.5 mm.
[0053] The polishing surface of the resulting polishing layer 4 is subjected to groove processing as required.
[0054] Thereafter, a double-sided tape is attached to the surface of the polishing layer 4 opposite to the polishing surface of the polishing layer 4 obtained in this manner. There are no particular limitations on the double-sided tape, and any double-sided tape known in the art can be selected and used.
[0055] <Method of manufacturing base layer 6> As described above, the material of the base layer 6 is polyurethane foam or a polyurethane material in which hollow microspheres are dispersed. The polyurethane foam to be used may be a commercially available product, or may be produced in the same manner as described in the method for producing the polishing layer 4 and used. The polyurethane material having hollow microspheres dispersed therein may be a commercially available product, or, when hollow microspheres are used, a polyurethane material having hollow microspheres dispersed therein may be produced in the same manner as described in the method for producing the polishing layer 4 and used.
[0056] The hollow microspheres that may be used for the base layer 6 are hollow microspheres that have an outer shell and are hollow inside. As the material of the hollow microspheres, commercially available products may be used, or products obtained by synthesis using a conventional method may be used. The material of the outer shell of the hollow microspheres is not particularly limited, and examples thereof include polyvinyl alcohol, polyvinylpyrrolidone, poly(meth)acrylic acid, polyacrylamide, polyethylene glycol, polyhydroxyether acrylate, maleic acid copolymer, polyethylene oxide, polyurethane, poly(meth)acrylonitrile, polyvinylidene chloride, polyvinyl chloride and organic silicone resins, and copolymers of two or more types of monomers that constitute these resins (e.g., acrylonitrile-vinylidene chloride copolymers, etc.). In addition, examples of commercially available hollow microspheres include, but are not limited to, Expancel series (trade name manufactured by Akzo Nobel), Matsumoto Microsphere (trade name manufactured by Matsumoto Yushi Co., Ltd.), etc. The gas contained in the hollow microspheres is not particularly limited, but may be, for example, a hydrocarbon, specifically, isobutane.
[0057] The shape of the hollow microspheres is not particularly limited, and may be, for example, spherical or nearly spherical. The average particle size of the hollow microspheres is not particularly limited, but is preferably 5 to 200 μm, more preferably 5 to 80 μm, further preferably 5 to 50 μm, and particularly preferably 5 to 35 μm. The average particle size can be measured by a laser diffraction particle size distribution analyzer (e.g., Mastersizer 2000, manufactured by Spectris Co., Ltd.).
[0058] The material for the hollow microspheres is added in an amount of preferably 0.1 to 10 parts by mass, more preferably 1 to 5 parts by mass, and even more preferably 1 to 4 parts by mass, based on 100 parts by mass of the urethane prepolymer.
[0059] In addition to the above components, a conventionally used blowing agent may be used in combination with the hollow microspheres within the range not impairing the effects of the present invention, and a gas that is non-reactive with the above components may be blown in during the mixing step described below. In addition, the foam or hollow microspheres of the base layer 6 have an advantage that there is no risk of peeling due to the slurry permeating into the base layer 6, since the foam or hollow microspheres are closed cells.
[0060] <Joining process> In the bonding step, the formed polishing layer 4 and base layer 6 are bonded (bonded) with an adhesive layer 7. For example, an acrylic adhesive is used for the adhesive layer 7, and the adhesive layer 7 is formed to a thickness of 0.1 mm. That is, the acrylic adhesive is applied to the surface of the polishing layer 4 opposite the polishing surface to a substantially uniform thickness. The surface of the polishing layer 4 opposite the polishing surface and the surface of the base layer 6 are pressed against each other via the applied adhesive, and the polishing layer 4 and base layer 6 are bonded with the adhesive layer 7. Then, after cutting into a desired shape such as a circle, an inspection is performed to confirm that there is no dirt or foreign matter attached, and the polishing pad 3 is completed.
[0061] <About the workpiece> The polishing pad 3 described in the present specification can be used for the object 8 to be polished, but is not particularly limited to the object 8 to be polished that is easily affected by the wavy shape. The object 8 to be polished that is easily affected by the wavy shape is an object 8 to be polished that has a metal film on its surface, and the polishing pad 3 described in the present specification can be used to polish such a metal film. The workpiece 8 may be a wafer having a layer of easily etchable SiO2 on which a metal film is formed. The metal of the metal film is not particularly limited, but is preferably a highly conductive metal such as gold, silver, or copper. EXAMPLES
[0062] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0063] In each of the examples and comparative examples, unless otherwise specified, "parts" means "parts by mass".
[0064] In addition, the NCO equivalent is a value indicating the molecular weight of the prepolymer (PP) per NCO group, which is calculated by (mass (parts) of polyisocyanate compound + mass (parts) of polyol compound) / [(number of functional groups per molecule of polyisocyanate compound × mass (parts) of polyisocyanate compound / molecular weight of polyisocyanate compound)-(number of functional groups per molecule of polyol compound × mass (parts) of polyol compound / molecular weight of polyol compound)].
[0065] (About the polishing layer) The same polishing layer A was used in all of the examples and comparative examples. The polishing layer A was manufactured as follows. 50 parts of an isocyanate-terminated urethane prepolymer having an NCO equivalent of 560, which is obtained by reacting 2,4-tolylene diisocyanate (TDI), polypropylene glycol (PPG) having a number average molecular weight of 1000, and diethylene glycol (DEG), and 50 parts of an isocyanate-terminated urethane prepolymer having an NCO equivalent of 600, which is obtained by reacting 2,4-tolylene diisocyanate (TDI), a polyester diol of adipic acid having a number average molecular weight of 2000 and 1,4-butanediol, and diethylene glycol (DEG), were mixed, and 3.5 parts of unexpanded hollow microspheres, the shell of which is made of an acrylonitrile-vinylidene chloride copolymer and in which isobutane gas is contained in the shell, were added and mixed to obtain a mixed liquid. The obtained mixed liquid was charged into a first liquid tank and kept warm. Next, 20.3 parts of MOCA was added as a curing agent to the second liquid tank separately from the first liquid, and kept warm in the second liquid tank. The liquids in the first liquid tank and the second liquid tank were each injected into a mixer equipped with two injection ports so that the R value, which represents the equivalent ratio of the amino group and hydroxyl group present in the curing agent to the terminal isocyanate group in the prepolymer, was 0.90. The two injected liquids were mixed and stirred while being injected into the mold of a preheated molding machine, and then the mold was closed and heated at 80°C for 30 minutes to perform primary curing. After the primary cured molded product was demolded, it was secondary cured in an oven at 120°C for 4 hours to obtain a urethane molded product. The obtained urethane molded product was allowed to cool to 25°C, and then heated again in an oven at 120°C for 5 hours, and then sliced to a specified thickness to obtain a polishing layer A. Thicknesses of 1.3 mm, 1.6 mm, and 2.0 mm were prepared, respectively.
[0066] (About the base layer) Substrates A to F to be used as substrate layers were prepared. Substrate A: Commercially available sponge-like urethane foam (Sekisui Chemical Co., Ltd. "Sekisui Sponge 2504KMS", A hardness 60, density 0.55g / cm 3 (Adjusted to have thicknesses of 0.8mm and 1.3mm) Substrate B: Balloon-foamed rigid urethane (100 parts of an isocyanate-terminated urethane prepolymer with an NCO equivalent of 460, which is made by reacting 2,4-tolylene diisocyanate (TDI), poly(oxytetramethylene) glycol (PTMG) with a number-average molecular weight of 650, and diethylene glycol (DEG), was mixed with 4.0 parts of the same hollow microspheres (unexpanded hollow microspheres) used in the polishing layer, and 41.8 parts of a 1:1 mixture of MOCA and PTMG with a number-average molecular weight of 1000 was added as a curing agent, and the same method was used to prepare the polishing layer). Hardness A: 80, density: 0.75 g / cm 3 , thickness 1.0mm) Substrate C: Commercially available sponge-like urethane foam (Sekisui Sponge 2504GMS manufactured by Sekisui Chemical Co., Ltd., A hardness 71, density 0.65 g / cm 3 , thickness 1.0mm) Substrate D: Commercially available sponge-like urethane foam (Sekisui Chemical Co., Ltd. "Sekisui Sponge 2504MP4", A hardness 72.5, density 0.52 g / cm 3 , thickness 1.0mm) Substrate E: Spongy low-resilience urethane ("Volara VSC" manufactured by Sekisui Chemical Co., Ltd., A hardness 65, density 0.19 g / cm 3 , thickness 0.8mm) Base material F: Spongy low-resilience urethane ("Volara S" manufactured by Sekisui Chemical Co., Ltd., A hardness 46, density 0.19 g / cm 3 , thickness 0.8mm)
[0067] (Measurement of compression deformation amount) For the substrates A to F, a continuous compression / recovery test was carried out using a MAG (Micro Autograph, Shimadzu Corporation, MST-1) to measure the amount of compression deformation. The amount of compression deformation was calculated by subtracting the thickness of the substrate layer before the test from the thickness of the substrate layer after the 100th compression. The results are shown in Table 1. The measurement conditions for MAG are as follows. Load: 50g / cm at recovery 2 , 300g / cm when compressed 2 ·Indenter: Diameter 20mm Sample: diameter 40mm Compression speed: 0.3mm / min Number of cycles: 100
[0068] (Measurement of storage modulus of substrate) A dynamic viscoelasticity test was carried out using RSA-G2 manufactured by TA Instruments to measure the storage modulus of each of the substrates A to F. The results are shown in Table 1. The measurement conditions for the storage modulus test are as follows. Frequency: 1Hz Sample: Length 10mm x Width 10mm x Thickness 0.1cm Test mode: Compression ·Measurement temperature: 40℃ Distortion range: 0.10% Initial load: 100g (Measurement of storage modulus of polishing layer) A dynamic viscoelasticity test was carried out on the polishing layer A using RSA-G2 manufactured by TA Instruments under the following measurement conditions to measure the storage modulus, which was 98.2 MPa. Frequency: 1.6Hz Sample: Length 50mm x Width 5mm x Thickness 0.16cm Test mode: Tensile ·Measurement temperature: 40℃ Distortion range: 0.10% ·Initial load: 148g
[0069] (Shore A hardness measurement) The Shore A hardness of the substrate was determined in accordance with the Japanese Industrial Standards (JIS K 7311) from the indentation depth of a pin pressed against the surface of the test piece via a spring.
[0070] [Table 1]
[0071] Examples and Comparative Examples The polishing layer A obtained above and substrates A to F as the base layer were joined with 0.1 mm thick double-sided tape (a PET substrate with an adhesive layer made of acrylic resin on both sides), and the double-sided tape was attached to the side of the substrate layer opposite the adhesive layer to produce the polishing pads of the examples and comparative examples.
[0072] (Polishing test) Polishing was performed under the following polishing conditions using the polishing pads of each Example and Comparative Example. The thickness of the Cu film was measured at 121 points on the diameter during polishing. FIG. 6 shows the profile of the Cu film thickness at the edge of the polished object polished using the polishing pads of the Examples and Comparative Examples. The vertical axis indicates the thickness of the Cu film, and the horizontal axis indicates the distance from the center of the straight line (diameter) passing through the center of the polished object (the center of the polished object is set to 0, and the part 140 to 150 mm from the center). For ease of comparison, the profiles of each Example and Comparative Example are shown in parallel for convenience. Compared to the Comparative Examples, the polishing pads of the Examples have a small film thickness difference of less than 350 angstroms, are straight even when approaching the edge, and the Cu film thickness is stable.
[0073] (polishing conditions) Grinding machine: F-REX300X (manufactured by Ebara Corporation) Disk: 34R (KINIK) Retainer ring: Retainer ring GXKD (manufactured by Ebara Corporation) Rotation speed: (table) 90 rpm, (polishing head) 81 rpm Grinding pressure: 1.6psi Polishing agent temperature: 20℃ Abrasive discharge rate: 200ml / min Abrasive: Cu slurry Polished object: Silicon wafer with Cu film (disc shape with a diameter of 300 mm) Polishing time: 60 seconds Pad break: 32N 20 minutes Conditioning: Ex-situ 32N2 scan
[0074] The film thickness difference obtained in the examples and comparative examples was determined by obtaining an edge profile after the above-mentioned polishing test, and measuring the distance from the most raised part of the edge to the most polished part, as shown in FIG. 4, as the "film thickness difference."
[0075] [Table 2]
[0076] From Tables 1, 2 and Figure 6, it can be seen that the polishing pads of Examples 1 to 4, which use substrates with a large storage modulus and a small amount of compressive deformation, have smaller film thickness differences, are straight even near the ends, and have stable Cu film thicknesses than the polishing pads of Comparative Examples 1 and 2, which use substrates with a storage modulus of less than 3.5 MPa and a large amount of compressive deformation.
[0077] Next, a polishing pad was created by combining layers of different thicknesses, using substrate A (thickness 0.8mm, 1.3mm) for the substrate layer and polishing layer A (thickness 1.3mm, 1.6mm, 2.0mm) for the polishing layer, and a polishing test was performed. The combinations are as follows. The results are shown in Table 3.
[0078] [Table 3]
[0079] From Table 3, it can be seen that when the thickness of the base layer relative to the thickness of the polishing layer is 40% or more and less than 65%, the film thickness difference is small, the film is straight even approaching the end, and the thickness of the Cu film is stable. [Industrial Applicability]
[0080] INDUSTRIAL APPLICABILITY The present invention provides a polishing pad that makes it possible to improve the profile abnormality of the edge portion, that is, the ridge shape, and thus contributes to the manufacture and sale of polishing pads and has industrial applicability.
[0081] 1 Polishing equipment 3 Polishing Pads 4 Polishing layer 6 Base material layer 7 Adhesive layer 8 Object to be polished 8a Wing Shape 9. Slurry 10 Polishing plate 11 Foundation 16 Holding Plate
Claims
1. A polishing pad comprising a polishing layer having a polishing surface for polishing an object to be polished, and a base layer disposed on the opposite side of the polishing surface of the polishing layer, The base layer has a compressive deformation of 20 μm or less in a compression test using MAG, The storage modulus is 3.5 MPa or more and 20 MPa or less in a dynamic viscoelastic measurement in a compression mode, A polishing pad, wherein the thickness of the base layer is 40% or more and less than 65% of the thickness of the polishing layer.
2. 2. The polishing pad according to claim 1, wherein the ratio of the storage elastic modulus of the polishing layer to the storage elastic modulus of the base layer (polishing layer / base layer) is 5 or more and 30 or less.
3. 2. The polishing pad of claim 1, wherein the substrate layer is made of a polyurethane foam or a polyurethane material having hollow microspheres dispersed therein.
4. 10. The polishing pad according to claim 1, which is a polishing pad for metal polishing.
5. A polishing method for polishing a workpiece having a metal surface, comprising the steps of: Providing an object to be polished having a metal surface; and a step of contacting the polishing surface of the polishing pad according to claim 1 with the metal surface to polish the metal surface.
Citation Information
Patent Citations
Polishing pad and method of polishing semiconductor wafer
JP2012000714A
Polishing pad
JP2016190313A